Accelerated Hypertension after Venlafaxine Usage - Yüksel Kıvrak; Tolga Sinan Güvenç; Nurcihan Akbulut; İbrahim Yağcı; Gülşen Çığşar; Süleyman Gündüz; Bahattin Balcı (Case Reports in Psychiatry)
Venlafaxine is the first antidepressant that acts via inhibiting serotonin and noradrenaline reuptake. Hypertension is observed in doses exceeding 300 mg/day and is the most feared complication. We report a patient with accelerated hypertension after venlafaxine use observed at a dose of 150 mg/day. A 23-year-old patient with symptoms of insomnia, depression, anhedonia, fatigue admitted our clinic. Venlafaxine at a dose of 75 mg/day was initiated after he was diagnosed with major depressive disorder. After 5 months, venlafaxine dose was uptitrated to 150 mg/day due to inadequate response to drug. After using venlafaxine for ten months at the dose of 150 mg/day, he admitted our clinic with headache and epistaxis. He was hospitalized after his blood pressure was measured as 210/170 mmHg. No secondary causes for hypertension were found, and venlafaxine treatment was considered possible etiologic factor. After stopping venlafaxine treatment, his blood pressure was reverted back to normal limits. While mild elevation of blood pressure could be observed after venlafaxine treatment, this case shows that accelerated hypertension with a diastolic blood pressure rise above 120 mmHg could be observed at relatively low doses of venlafaxine. Close monitoring of blood pressure is necessary after initiation of treatment, as accelerated hypertension could cause endorgan damage with potentially catastrophic results.